Molecular structure and vibrational spectra of [2-Oxo-2-(4-acetyl) phenyl amino] ethylene methacrylate by density functional theory and ab initio Hartree-Fock calculations - Yakuphanoğlu, Fahrettin; Atalay, Y; Erol, I (Taylor & Francis Ltd, 2005)
The molecular geometry and vibrational frequencies of the [2-Oxo-2-(4-acetyl) phenyl amino] ethylene methacrylate (APEMA) were examined theoretically using the Hartree-Fock and Density function method (B3LYP) with 6-31G(d) basis set. The calculated geometrical parameters of the investigated molecule were compared with experimental data. Both the calculated structural parameters and vibrational frequencies are in good agreement with the available experimental data.
Keywords: Heterocyclic Methacrylates; Water-Absorption; Frequencies; Polymers